DESIGN AND PROPERTIES OF SPLIT MASTIC ASPHALT MODIFIED WITH RETONA AT HOT AND ARID REGION - A. A. Almahdi, Mohammed; Setyawan, Ary; Yulianto, Budi (Jurnal Teknik Sipil, 2014)
AbstractThe use of Retona as the additive material in the hot mix split mastic asphalt with a certain comparison is expected to improve the quality of the split mastic asphalt. This study aimed to determine the extent of Marshall properties (Stability, Flow, Marshall Quotient, VITM, VFWA, and Air Void), ITS and UCS test at (30ºC, 40ºC, 60ºC) and Permeability Test. The objective of that is a comparing the results between SMA (AC 60/70) and SMA modified with retona to know the properties if to be used at hot and arid region. In comparison with the results of Marshall Test SMA modified with Retona and SMA (AC60/70) are : the stability value is higher by 11.52%, the flow value is lower by 11.89%, the marshall qoutient value is higher by 26.65%, the VITM value is lower by 1.93%, the VFWA value is higher by 90.57%, and the Air Void value is lower by 9.34%. The ITS value of SMA without Retona is higher than SMA with Retona is 49.28 % at temperature 40oC. The UCS value of SMA without Retona is higher than SMA with Retona is 18.99 % at temperature 30oC. The SMA modified with Retona is less sensitive to temperature changes by using ITS and UCS test compared with SMA without Retona. The coefficient of permeability value of SMA with Retona is higher than SMA without Retona 294% at water pressure 10000 dyne/cm² and by 348 % at water pressure 20000 dyne/cm². Where find that the mixtures are Practically impervious.Keywords: Split Mastic Asphlat (SMA), Retona, Marshall Test, ITS & UCS Test , Permeability test.